Integrity of head and tail plasmalemma is associated with different kinetic variables in boar sperm - Grieblová, Adéla; Pintus, Eliana; Ros-Santaella, José Luis (Animal reproduction science, 2017)
An intact and functional sperm plasmalemma has a major role in sperm motility and fertilizing capacity. Several techniques have been developed to evaluate the integrity of the sperm plasma membrane, but there are still some inconsistencies concerning the methods that are more closely associated with sperm function. In this study, the aim was to: i) evaluate the integrity of the boar sperm plasmalemma during 72h of semen storage at 17°C using four techniques: eosin/nigrosin (E/N), propidium iodide/carboxyfluorescein diacetate (PI/CFDA), hypo-osmotic swelling test (HOST), and combined HOST with eosin staining (HOST/E), ii) assess the correlations and the limits of consistency among these techniques, iii) and estimate the relationships with the acrosomal status and sperm kinetics. Results indicate that the integrity of the sperm plasmalemma decreases during 72h of storage, although significant differences were found only using the HOST and HOST/E techniques. Moreover, use of E/N and PI/CFDA results in greater values relative to the undamaged sperm membrane than use of HOST and HOST/E at any incubation time. Overall, results using all techniques were consistent and correlate except for findings with PI/CFDA and HOST, which was slightly below 95%. Moreover, values using the techniques for the evaluation of the integrity of the sperm head and tail membranes are positively associated with the acrosomal status and different kinetic variables with the tail integrity being related to rapid linear trajectories and the head integrity to rapid curvilinear trajectories. The results of this study provide new insights into the relevance of evaluating the boar sperm plasmalemma in the routine spermiogram.
Keywords: prasata; Swine; Temperature; hlavička spermie; Male; Semen Analysis; Sperm Motility; Sperm viability; Sperm velocity; Spermatozoa; Semen storage; odběr biologického vzorku; mužské pohlaví; Time Factors; Cell Membrane; Animals; Pig; Sperm Head; zvířata; Specimen Handling; motilita spermií; buněčná membrána; časové faktory; spermie; Sperm lifespan; teplota; Plasma membrane; analýza spermatu